Characterization of cell-binding properties of bovine herpesvirus 1 glycoproteins B, C, and D: identification of a dual cell-binding function of gB. - Li, Y (1995)
Previous studies have suggested that the attachment of bovine herpesvirus 1 (BHV-1) to permissive cells is mediated by its major glycoproteins B (gB), C (gC), and D (gD). In order to gain further insight into the mechanism of the BHV-1 attachment process, we purified authentic gB, gC, and gD from BHV-1-infected cells and membrane anchor-truncated, soluble gB, gC, and gD from stably transfected cell lines by affinity chromatography and examined their cell-binding properties on Madin-Darby bovine kidney cells. All of the glycoproteins tested exhibited saturable binding to Madin-Darby bovine kidney cells. All of the glycoproteins tested exhibited saturable binding to Madin-Darby bovine kidney cells. Addition of exogenous heparin or treatment of cells with heparinase to remove cellular heparan sulfate (HS) prevented both gC and gB from binding to cells but had no effect on gD binding. An assessment of competition between gB, gC, and gD for cell binding revealed that gC was able to inhibit gB binding, whereas other combinations showed no effect. Cell-bound gC could be dissociated by heparin or heparinase treatment. The response of bound gB to heparin and heparinase treatments differed for the authentic and soluble forms; while soluble gB was susceptible to the treatment, a significant portion of cell-bound authentic gB was resistant to the treatment. Binding affinity analysis showed that soluble gB and both forms of gC and gD each had single binding kinetics with comparable dissociation constants (Kds), ranging from 1.5 x 10(-7) to 5.1 x 10(-7) M, whereas authentic gB exhibited dual binding kinetics with Kd1 = 5.2 x 10(-7) M and Kd2 = 4.1 x 10(-9) M. These results demonstrate that BHV-1 gC binds only to cellular HS, gD binds to a non-HS component, and gB initially binds to HS and then binds with high affinity to a non-HS receptor. Furthermore, we found that while authentic gB was able to inhibit viral plaque formation, soluble gB, which retains the HS-binding property but lacks the high-affinity binding property, was defective in this respect. These results suggest that the interaction between gB and its high-affinity receptor may play a critical role in the virus entry process.